Análise comparativa de técnicas de recuperação ambiental em áreas degradadas no município de Bofete/SP - Castelli, Karen Regina [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Areas used for cultivation of commercial forest plant species subjected to environment recovery activities have constituted a rare scenário not yet well established in Brazil. Little information is provided in terms of ecological indicators where the recovery process has started in such areas, specially about the floristic, edaphic and climatologic features. In this study, the ecological indicators have been compared in areas where has been applied three methods of environmental restoration (soil transposition (ST), aritificial perches (PER), and areas with native vegetation (REF). The four areas are located in a rural one in Bofete, state of São Paulo, Brazil. The data regarding phytosociological, edaphic and microclimatic attributes have been surveyed. The soil is sandy-textured with an inexpressive spatial variation of the particle-size distribution and degree of comparison on the soil. The chemical attributes have indicated fertility significantly low in the PER and REF, and the soil of the EUC plot has been the most fertile. It has been identified 52 plant species, with 29 species in REF area, 28 in EUC, 8, in ST and 7, in the PER parcels. Only one species has been common in all study areas (Siparuna guianensis). The Shannon index values are: 1.05 (REF), 1.17 (EUC), 0.65 (ST) and 0.58 (PER). The Jaccard index was higher than 50% between REF and EUC areas, evidencing low similarity among the floristic composition of such areas. It has been observed where the light incidence and wind velocity values were higher (PER e ST), the floristic diversity were smaller. The set of species has been mostly composed of species of initial stages of ecosystem regeneration. Up to now, the recovery methods ST and PER have evidenced low effectiveness in recovering the degraded areas. The most promising action might be to keep the eucalypts woodland alilve, selectively pruning them and keeping the wood and herbaceous understory in continous growth

As áreas usadas para plantio de espécies florestais comerciais que foram submetidas às atividades de recuperação ambiental ainda constitui um cenário raro no Brasil e muito pouco se sabe em termos de indicadores ecológicos destas áreas após o início do processo de recuperação, especialmente sobre os aspectos forísticos, edáficos e climatológicos. Desta forma, compararam-se indicadores ecológicos em três áreas submetidas e diferentes métodos de recuperação ambiental (transposição de solo (TS), poleiros artificiais (POL) e bosque abandonado de eucalipto (EUC) e uma área com vegetação nativa utilizada como referência (REF). As quatro áreas localizam-se numa propriedade rural no município de Bofete-SP. Em cada área levantou-se informações sobre os atributos fitossociológicos, edáficos e microclimáticos. O solo é de textura arenosa e com inexpressiva variação na composição granulométrica e grau de compactação entre as áreas de estudo. Os parâmetros químicos indicaram fertilidade significativamente baixa nas áreas POL e REF, sendo o solo de área EUC, o mais fértil. Foram identificadas 50 espécies arbóreas, sendo 29 espécies na área REF, 28 na área EUC, 8 na TS e 7 na POL. Apenas uma espécie foi comum a todas as áreas de estudo (Siparuna guianensis). O índice de Shannon variou em 1,05 (REF), 1,17(EUC), 0,65 (TS) e 0,58 (POL). O índice de Jaccard foi maior que 50% apenas na comparação entre as áreas REF e EUC, demonstrando baixa similaridade entre a composição florística das áreas. Observou-se que as áreas onde os valores de incidência luminosa e velocidade do vento foram maiores (POL e TS), exibiram menor diversidade florística, sendo essa composta apenas por espécies de estágios iniciais de regeneração. Os métodos de recuperação TS e POL não evidenciaram até o momento, eficiência na recuperação das áreas degradadas. A ação mais promissora seria manter o bosque com...
Comparative analysis of the environmental recovery techniques in degraded areas in the city of Bofete/SP
Keywords: Qualidade ambiental; Florestas; Solos; Environmental quality